(untitled) (Journal of Economic Research & Business Administration, 2017)
The paper discusses the domestic high-tech projects, the successful implementation of which will enhance the competitiveness of the economy. As is known, high-tech projects implement in the field of complex technical systems and have different knowledge-intensive, high technical risks and unpredictable results. In this regard, the implementation of domestic high-tech projects faces a number of obstacles that can solved with the help of the integrated use of project management methods. The study found that many domestic rather promising projects in the first stage of development provide significant results, but then after influences of various factors lose their previous pace and lagging behind in terms that exceed a predetermined budget or lead to other disastrous results. The authors proposed a number of ways that will help improve the situation in the market of high-tech projects.